Kepuasan Pelanggan Ritel Tradisional : Peran Harga, Variasi Produk, Pelayanan, dan Pengaruhnya terhadap Loyalitas serta Perilaku Pembelian Konsumen - Mubarok, Rizkul; Muslikhun, Alfin (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aimed to determine the impact of price, product variety and service quality on customer satisfaction at Warung Pojok grocery stores in Semarang. The study adopted an explanatory approach. The sample size was calculated using the Lemeshow formula and comprised 120 Warung Pojok customers. Multiple linear regression was used to analyse the data. The results showed that price had no significant effect on customer satisfaction. Conversely, product variety and service quality were found to have a positive and significant effect on customer satisfaction. These findings confirm that product diversity and quality service are important in fostering customer loyalty within the traditional retail sector. In practical terms, the results can help business owners to formulate marketing strategies tailored to consumer needs. Furthermore, these findings can serve as a reference for future studies examining customer satisfaction factors in the context of grocery stores. In practical terms, the results can assist business owners in formulating targeted marketing strategies that prioritize product variety and service excellence. The study also provides valuable insights for future research, offering a foundation for further exploration of customer satisfaction factors in grocery store contexts and other traditional retail environments.